The effects of instruction and environmental demand on state anxiety, driving performance and autonomic activity: Are ego-threatening manipulations effective? - Barnard, Megan Patricia; Chapman, Peter (Elsevier, 2018)
A small yet emerging body of research on the relationship between anxiety and driving suggests that higher levels of state anxiety may lead to more dangerous driving behaviours. The aim of the current research was to investigate the effects of increased state anxiety on driving behaviours within a simulated environment using instructional sets to manipulate anxiety levels. In Study One, whilst a set of safety-related instructions were able to increase state anxiety, this did not result in changes to driving behaviours. In Study Two, ego-threatening instructions were not able to successfully increase state anxiety. This has implications regarding instructional sets in research, including their task relevance and the necessity for a motivational incentive. However, when changes in anxiety were considered regardless of instruction group, Study Two found changes in SDLP and skin conductance levels related to state anxiety increases. As these effects were context specific, it is argued that some of these changes may be due to poorer processing efficiency, leading to suggestions about the types of behaviours that may need to be trained in potential therapies for those who show high state anxiety levels whilst driving.